PENGARUH PERMAINAN TRADISIONAL ENGKLEK SMART TERHADAP MINAT BACA ANAK KELOMPOK B RA AL-HUDA SUMBERAGUNG, SUKODADI, LAMONGAN - Barokatun Ni’mah; Ervin Nurul Affrida (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This research was motivated by the low reading interest among children aged 5-6 years. Based on observations made during observations at RA Al Huda Sumberagung, Sukodadi, Lamongan, in terms of reading, group B children have not developed according to expectations. This was identified as group B children tending to lack enthusiasm when learning to read, because of the media used by the teacher. when reading only consists of books and a blackboard. The aim to be achieved in this research is to determine the influence of the traditional game engklek smart on the reading interest of children in group B RA Al Huda Sumberagung, Sukodadi, Lamongan. This research uses a quantitative research approach with a pre-experimental research type using a one group pretest-posttest design. The research subjects were group B children at RA Al Huda Sumberagung, Sukodadi, Lamongan with a total of 9 children. The data collection method used is observation using assessment tools in the form of observation sheets and documentation. Using statistical analysis methods with the formula used is the t test which corresponds to the title The Influence of the Traditional Game Engklek Smart on Reading Interest in Group B Children RA Al Huda Sumberagung, Sukodadi, Lamongan Data analysis technique uses the t test The calculation results show that the t value = 12.67 and the t table is 1.86 for a significance level of 0.05 and 2.90 for a significance level of 0.01. From these results it can be seen that the tcount value is greater than ttable, thus the Null Hypothesis is rejected and the Working Hypothesis is accepted. So, it can be concluded that the traditional game engklek smart influences the reading interest of children in group B RA Al Huda Sumberagung, Sukodadi, Lamongan.